2018
DOI: 10.18410/jebmh/2018/300
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of 150 Elderly Patients With Acute Myocardial Infarction

Abstract: BACKGROUNDThe longevity has increased in India and is further going to rise. The elderly are living with medical, social and psychological problems. Acute myocardial infarction in elderly often presents with atypical presentation and hence leads to delay in diagnosis and increased mortality. The presence of multiple comorbidities adds to increased morbidity and low quality of life. Acute myocardial infarction is leading cause of death in elderly in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Savith et al 21 noted Non-ST elevation MI in 4% of their patients. Ambali et al 22 noted STEMI in 109 (72.6%) and NSTEMI in 41 (27.4%) of their subjects. Bhatia LC et al 19 observed, electrocardiographic presentation differed in the elderly.…”
Section: Ecg Findingsmentioning
confidence: 88%
See 3 more Smart Citations
“…Savith et al 21 noted Non-ST elevation MI in 4% of their patients. Ambali et al 22 noted STEMI in 109 (72.6%) and NSTEMI in 41 (27.4%) of their subjects. Bhatia LC et al 19 observed, electrocardiographic presentation differed in the elderly.…”
Section: Ecg Findingsmentioning
confidence: 88%
“…Savith et al 21 observed elevated CKMB in 70% of the patients and elevated Troponin I in 48% of patients. Ambali et al 22 observed creatinine Phosphokinase MB to be elevated in 126 (84%) patients, while Troponin-T was positive in 90 (60%) of the patients.…”
Section: Biochemical Investigationsmentioning
confidence: 98%
See 2 more Smart Citations
“…These challenges pose difficulty in diagnosing AMI by treating physicians in elder patients. 9 It has been found that STEMI type of AMI is globally the most important cause of death and morbidity. 10…”
Section: Introductionmentioning
confidence: 99%